2022
DOI: 10.1007/s11469-022-00908-9
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonally-Based Fears and Problematic Social Networking Site Use: The Moderating Role of Online Social Support

Abstract: Within the Compensatory Internet Use Theory (CIUT) framework, online activities may compensate for psychosocial problems. However, those who attempt to satisfy their needs or mitigate their fears via Social Networking Sites (SNSs) may be at heightened risk for problematic use of SNSs (PSNSU), especially in cases when these fears have an interpersonal basis, and the individual effectively finds online social support. The current study hypothesizes that interpersonally-based fears (i.e., fear of no mattering, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…When faced with stressful events, many individuals resort to the overuse of the internet (such as through smartphone addiction) as a means to release psychological pressure. [56][57][58][59] Consequently, individuals experiencing negative emotions (eg, depression) are more inclined to employ the internet (eg, smartphone addiction) in order to mitigate stress and alleviate negative emotions. Empirical studies have consistently demonstrated that depression constitutes a significant risk factor for smartphone addiction.…”
Section: The Mediating Role Of Social Painmentioning
confidence: 99%
See 1 more Smart Citation
“…When faced with stressful events, many individuals resort to the overuse of the internet (such as through smartphone addiction) as a means to release psychological pressure. [56][57][58][59] Consequently, individuals experiencing negative emotions (eg, depression) are more inclined to employ the internet (eg, smartphone addiction) in order to mitigate stress and alleviate negative emotions. Empirical studies have consistently demonstrated that depression constitutes a significant risk factor for smartphone addiction.…”
Section: The Mediating Role Of Social Painmentioning
confidence: 99%
“…84 In line with compensatory internet use theory, individuals experiencing depression tend to engage in excessive internet use (smartphone addiction) as a means to alleviate their depressive symptoms. [56][57][58][59] Problematic internet use (eg, smartphone addiction) can be seen as an escape response to negative life events. 85 When adolescents faced with negative emotional reactions such as depression, they might adopt maladaptive coping strategies in order to release psychological stress and relieve negative emotions by excessively relying on mobile phones.…”
Section: The Mediating Role Of Social Painmentioning
confidence: 99%
“…Among 8,912 college students across seven countries (U.S., Canada, Spain, England, Argentina, Uruguay, and South Africa) high ruminating thoughts have accounted for major depressive and social anxiety symptoms ( 31 ). Several studies have shown an association between low self-esteem ( 32 , 33 ) and fear of negative self-evaluation ( 34 ) anxiety ( 35 ) and problematic SNS use.…”
Section: Emotional and Social Factors Associated With Problematic Sns...mentioning
confidence: 99%